Disseminated Intravascular Coagulation after Surgery for Facial Injury - Hisashi Ozaki; Hirohiko Tachibana; Shigeo Ishikawa; Kazuyuki Yusa; Kenichirou Kitabatake; Mitsuyoshi Iino (Hindawi Limited, 2016)
A case of disseminated intravascular coagulation (DIC) presenting after surgery for facial trauma associated with multiple facial bone fractures is described. With regard to the oral and maxillofacial region, DIC has been described in the literature following head trauma, infection, and metastatic disease. Until now, only 5 reports have described DIC after surgery for facial injury. DIC secondary to facial injury is thus rare. The patient in this case was young and had no medical history. Preoperative hemorrhage or postoperative septicemia may thus induce DIC.